CULTURAL INTERCONNECTION IN VIRTUAL SPACE: TRANSFORMATION OF COLLECTIVE IDENTITY IN THE CODE-SWITCHING PHENOMENON IN COMMUNICATION SCIENCE STUDENTS OF UINSU - Ritonga, Rahmad Alfarizki; Rasyid, Abdul (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to explore the practice of code-switching as a form of cultural interconnection and collective identity transformation among Communication Science students of the State Islamic University of North Sumatra (UINSU) in virtual space. The phenomenon of code-switching not only reflects students' bilingual abilities but also becomes a communicative strategy in navigating social, cultural, and media algorithmic contexts. With a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and documentation of digital interactions. The analysis was carried out using the Miles, Huberman, and Saldana models, and was strengthened by data triangulation to ensure the validity of the findings. The results of the study show that students actively use code-switching as a form of dynamic and contextual identity expression. This practice is evident in the use of digital loanwords, the combination of languages in one utterance (intra-sentential switching), and expressions of popular cultural affiliation such as Japanese. In addition, code-switching is used to build social solidarity and adapt to the norms of online community communication. These findings also underline the linguistic awareness of students in distinguishing language use between formal and informal spaces. Theoretically, this study strengthens the sociolinguistic view that code-switching is not random, but strategic and meaningful in the process of forming social identity. This study is expected to be a reference in developing language education policies that are more adaptive to the dynamics of digital communication in the university environment.